2016
DOI: 10.1111/jpi.12307
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin relieves neuropathic allodynia through spinal MT2‐enhanced PP2Ac and downstream HDAC4 shuttling‐dependent epigenetic modification of hmgb1 transcription

Abstract: Melatonin (MLT; N-acetyl-5-methoxytryptamine) exhibits analgesic properties in chronic pain conditions. While researches linking MLT to epigenetic mechanisms have grown exponentially over recent years, very few studies have investigated the contribution of MLT-associated epigenetic modification to pain states. Here, we report that together with behavioral allodynia, spinal nerve ligation (SNL) induced a decrease in the expression of catalytic subunit of phosphatase 2A (PP2Ac) and enhanced histone deacetylase 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 48 publications
1
48
1
Order By: Relevance
“…A previous study demonstrated that SNL-enhanced spinal Fbxo3 expression underlies the development of neuropathic pain by affecting postsynaptic components of the spinal neural circuitry (Lin et al, 2015b). Moreover, the above results showed that pharmacological antagonism of spinal Fbxo3 alleviated SNL-induced allodynia by modifying presynaptic RIM1␣-dependent machinery.…”
Section: Bc-1215 Reduces Snl-enhanced Frequency and Amplitude Of Sepsmentioning
confidence: 54%
See 4 more Smart Citations
“…A previous study demonstrated that SNL-enhanced spinal Fbxo3 expression underlies the development of neuropathic pain by affecting postsynaptic components of the spinal neural circuitry (Lin et al, 2015b). Moreover, the above results showed that pharmacological antagonism of spinal Fbxo3 alleviated SNL-induced allodynia by modifying presynaptic RIM1␣-dependent machinery.…”
Section: Bc-1215 Reduces Snl-enhanced Frequency and Amplitude Of Sepsmentioning
confidence: 54%
“…Ligations of spinal nerves in rats were performed under isoflurane anesthesia (induction 5%, maintenance 2% in oxygen), following the methods of a previous study (Lin et al, 2016). After isoflurane anesthesia, rats were placed in a prone position.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations